Optimal placement of surge arresters for transmission lines lightning performance improvement - Castro, Walace S.; Lopes, Ivan J.S.; Missé, Silvio L.V.; Vasconcelos, João A. (Electric power systems research, 2022)
•The use of arresters can improve the lightning performance of transmission lines.•Placement based on the tower-footing impedance does not allocate arresters optimally.•Solutions use a minimum number of arresters to achieve a target lightning performance.•Transfer effect of the lightning surge due to arresters operation is rarely mentioned.•The number of arresters may be underestimated if the transfer effect is not included. Installation of transmission line surge arresters (TLSA) is one of the solutions found to improve the lightning performance of overhead transmission lines (OHTL). This work proposes a new multi-criteria methodology for the optimal placement of surge arresters on OHTL based on a multi-objective optimization algorithm coupled with ATP (Alternative Transient Program) software. Lightning performance calculation is performed considering the transfer effect of the lightning surge due to arresters operation. This transfer mechanism that can lead the adjacent towers to flashover is rarely mentioned in the literature. A case study considering a 230 kV transmission line with 231 towers and 105 km long operating in Brazil is presented. Compared to the real performance data, the solution found with the best cost-benefit ratio allows a reduction of 68% in the line outages with the use of 90 surge arresters (i.e., 0.86 TLSAs/km of line). This is practically 50% of the number of arresters calculated using the classical placement method based on the tower-footing impedance value. Regarding the transfer effect of the lightning surge, the results show that the performance levels and, consequently, the number of TLSAs to protect the line may be underestimated if this effect is not considered in the modelling.